PENDAMPINGAN MODEL HYBRID UNTUK PENGEMBANGAN GURU DI ERA DISRUPSI DIGITAL: MENJAWAB TANTANGAN AI DALAM PENDIDIKAN - Ikhsan Mubarok; Siti Aimah (DEVELOPMENT: Journal of Community Engagement, 2025)
This study aims to analyse the impact of artificial intelligence (AI) on the role of teachers and offer a hybrid model-based educator development strategy that maintains pedagogical essence in the era of digital disruption. The approach used is qualitative with the type of case study, at MTS At-Taufiq North Kundur. Data collection techniques include in-depth interviews, participatory observation, documentation, and document study. Data analysis uses the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawing, with validity checks through triangulation of sources, methods, and observers. The results showed that AI is not a threat, but rather a trigger for the transformation of the teacher's role into a more strategic learning facilitator. The hybrid model is proven to be effective in improving teachers' digital competence, but the inequality of access to technology is the main obstacle, especially in the 3T area. The contribution of this research lies in developing a technology-based educator development strategy that maintains human aspects, providing applicable recommendations for policy makers and educational institutions in optimising AI inclusively. Keywords:  AI, teachers, hybrid model, digital competency, education.